1999
DOI: 10.1159/000028766
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Atlantoaxial Instability: Management with Screw Fixation

Abstract: Sixteen pediatric patients (age range 3–15 years; mean 9.4 years) with atlantoaxial instability underwent screw fixation at Columbus Children’s Hospital between 1992 and 1998. Three patients with type II odontoid fractures underwent odontoid screw fixation. The remaining group of 13 patients had posterior C1-2 transarticular screw fixation and Sonntag C1-2 fusion. The group included 3 patients with rotatory C1-2 fixation, 4 patients with os odontoideum, 4 patients with congenital atlantoaxial instability and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 29 publications
2
46
0
2
Order By: Relevance
“…In the past, a C1-C2 fusion using autogenous iliac crest and sublaminar wiring such as Brooks-Jenkins, Gallie, and Sonntag have been reported [24][25][26], but this technique resulted in non-union in most cases, especially for patients with Down syndrome [1,2]. C1-2 transarticular screw fixation (Magerl technique [3]) and its effectiveness in pediatric patients have been described [8,16,17]. Similarly, some studies reported that the C1 lateral screw and C2 pedicle screw technique (Goel-Harms constructs [4,5]) provide stabilization and promotes fusion in pediatric patients with AAI [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, a C1-C2 fusion using autogenous iliac crest and sublaminar wiring such as Brooks-Jenkins, Gallie, and Sonntag have been reported [24][25][26], but this technique resulted in non-union in most cases, especially for patients with Down syndrome [1,2]. C1-2 transarticular screw fixation (Magerl technique [3]) and its effectiveness in pediatric patients have been described [8,16,17]. Similarly, some studies reported that the C1 lateral screw and C2 pedicle screw technique (Goel-Harms constructs [4,5]) provide stabilization and promotes fusion in pediatric patients with AAI [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Magerl et al [3] first proposed the use of C1-C2 transarticular screws in adults, and an alternative technique, namely C1 lateral mass screws and C2 pedicle screws [4,5] or C2 translaminar screws [6] has been reported. More recently, these techniques are being used in pediatric patients [7][8][9][10][11][12][13][14][15][16][17]; however, there are no detailed reports on the risks with these techniques when used in children. Furthermore, the medical community does not fully understand the long-term effects of posterior cervical spine fusion in the skeletally immature spine, and there are only a few published articles on these effects [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Diminutive osseous and ligamentous structures, as well as the peculiar configuration of vertebral components, the presence of congenital malformations with possible abnormal vertebral artery location, and the need for external immobilization and the potential for its complications have made it important to critically evaluate instrumentation and its incorporation into the management of pediatric patients who require craniocervical stabilization. 4,6,16,22,35,37 In the past, the use of bone (rib or iliac crest) with …”
mentioning
confidence: 99%
“…11,82,138,140 While there was a dearth of publications related to the use of allograft in pediatric cervical spine fusions for the 2 decades that followed the early failures reported in the 1980s, there has been a resurgence in interest over the most recent decade corresponding to the widespread use of rigid internal fixation techniques and the availability of BMP. 56,69,73,78,88,151 Emboldened by the greater fusion rates associated with screw-based constructs, with or without the use of BMP, there has been a sharp rise in publications describing OCF and PCF in children and adults. Our review confirmed that fusion rates greater than 90% have been routinely reported with pediatric OCF and PCF when allograft is used with rigid internal fixation.…”
Section: Publication Biasmentioning
confidence: 99%